Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1371/journal.pone.0199977
|View full text |Cite
|
Sign up to set email alerts
|

Patients experiences of self-management and strategies for dealing with chronic conditions in rural Malawi

Abstract: BackgroundThe high burden of chronic communicable diseases such as HIV/AIDS, and an escalating rise of non-communicable diseases (NCDs) in Malawi and other sub-Saharan African countries, calls for a shift in how health care services are designed and delivered. Patient-centred care and patient self-management are critical elements in chronic care, and are advocated as universal strategies. In sub-Saharan Africa, there is need for more evidence around the practice of patient self-management, and how to best supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 32 publications
1
46
0
Order By: Relevance
“…A study has shown a correlation between self-care of TB patients and socio-demographic factors, including gender, marital status, family structure, family support, income (19). Several studies have investigated factors affecting the self-management in patients with chronic disease and revealed the impacts of socio-demographic (age, education, job, income) knowledge, attitude, the presence of support from family and community, social relations and the ability to deal with stress and stigma on self management (20)(21)(22)(23)(24). It has been revealed that socio-demographic factors including age, education, occupation, family support, residential locality and income impact knowledge; Education and income were related to attitude (22,(24)(25)(26)(27).…”
Section: Introductionmentioning
confidence: 99%
“…A study has shown a correlation between self-care of TB patients and socio-demographic factors, including gender, marital status, family structure, family support, income (19). Several studies have investigated factors affecting the self-management in patients with chronic disease and revealed the impacts of socio-demographic (age, education, job, income) knowledge, attitude, the presence of support from family and community, social relations and the ability to deal with stress and stigma on self management (20)(21)(22)(23)(24). It has been revealed that socio-demographic factors including age, education, occupation, family support, residential locality and income impact knowledge; Education and income were related to attitude (22,(24)(25)(26)(27).…”
Section: Introductionmentioning
confidence: 99%
“…According to a study by Earnshaw et al, 28 the participants also revealed that acceptance of the illness and the use of medication is what enabled them to cope with the chronic illnesses. Moreover, in a study by Angwenyi et al 29 it was reported that in making a plan for management of HIV and hypertension as a chronic illness, the participants who were involved in the study had a high awareness regarding food restrictions, especially those living with hypertension, and PLWH were reported to consume a nutritious diet and following the diet plan as per their health provider’s instructions. The findings of this study were consistent with studies that have been conducted.…”
Section: Discussionmentioning
confidence: 99%
“…In low- and lower middle-income countries (LICs and LMICs) including in sub-Saharan Africa, South East Asia, and Latin America, patient’s ability to self-manage or cope with the chronic disease vary but may often be influenced by internal factors including spirituality, belief system, and religiosity, and external factors including appropriate knowledge of the disease, poverty, family support system, and one’s grit and social relations network. The support system comprising healthcare providers and caregivers plays a crucial role as most patients rely on them in making decisions, and for the necessary adjustments in their health behavior [ 13 ]. In LIC regions, where there are often a relatively low number of physicians and even lower number of kidney care providers per population especially in rural areas, a stepwise approach can involve local and national stakeholders including both non-governmental organizations and government agencies by (1) extending kidney patient education in rural areas, (2) adapting telehealth technologies if feasible to educate patients and train local community kidney care providers and (3) implementing effective retention strategies for rural kidney health providers including adapting career plans and competitive incentives.…”
Section: Living With Kidney Disease In Low-income Regionsmentioning
confidence: 99%